Listening to children about well-being - Vaz-Velho, Catarina (2020)
This paper discusses epistemological, ethical and methodological issues about the study of children’s well-being listening to the children themselves in a specific collaborative project between some researchers at the University of Évora, Hospital of Santarém and Évora’s Child Activity Centre (CAI), an early childhood education centre. The research aim was to explore and develop the concept of children’s well-being. The centrality of children as research participants was fundamental to our methodological approach. Using a qualitative perspective and qualitative methods we explored children understandings about well-being, of how and when it is experienced by them. We discuss some of the challenges and implications driven from the reflection on the research process in terms of the epistemological, ethical and methodological questions that were raised and how they were addressed in a study that took place in the Child Activity Centre.